Global financial crisis and the puzzling exchange rate path in CEE countries - Jesús Crespo Cuaresma; Adam Geršl; Tomáš Slačík (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In the present paper we examine whether financial markets could have helped predict exchange rates in three selected Central and Eastern European (CEE) economies of the EU, namely the Czech Republic, Hungary and Poland, during the current financial crisis. To this end, we derive risk-neutral densities from the implied volatilities of FX options, which approximate market expectations about exchange rate developments. Based on these risk-neutral density estimates, we then assess the out-of-sample predictive power of indicators. The forecasting results suggest that models based on FX options are inferior to the random walk in terms of the forecasting error, confirming a stylized fact about the short-term forecasting of exchange rates. Yet, we also find that, for the Czech Republic and Poland, risk-neutral densities contain useful information on the direction of change of the exchange rate.
Keywords: C11; C32; C53; F37; G14; G17; 330; options; implied volatility; risk-neutral density; exchange rate forecasting; Bayesian model averaging; subprime crisis; emerging markets; Devisenoption; Volatilität; Wechselkurs; Prognose; Finanzkrise; Tschechische Republik; Ungarn (Personen); Polen